Synthesis and characterization of a new cyclobutane-substituted Schiff base ligand and its Co(II), Cu(II) and Ni(II) complexes - Çukurovali, A; Yilmaz, I; Ahmedzade, M (Marcel Dekker Inc, 2000)
A new ligand, 4-(1-phenyl-1-methylcyclobutane-3-yl)-2-(2-hydroxy-5-bromo)benzylideneaminothiazole (LH), has been synthesized starting from 1-phenyl-1-methyl-3-(2-chloro-1-oxoethyl)cyclobutane, thiourea and 2-hydroxy-5-bromobenzaldehyde. Mononuclear complexes with a metal-ligand ratio of 1:2 have been prepared with Co(II), Cu(II), and Ni(II). Attempts to prepare the Cd(II) complex of the ligand in different solvents have failed. The authenticity of the ligand and its complexes was established based on elemental analyses, IR, C-13 and H-1 NMR spectra, UV-Vis, magnetic susceptibility measurements and thermogravimetric analyses (TGA).
Keywords: Derivatives